2017
DOI: 10.1177/0272684x17747053
|View full text |Cite
|
Sign up to set email alerts
|

Health-Promoting Behaviors and Their Predictors in Iranian Women of Reproductive Age: A Cross-Sectional Study

Abstract: Health-promoting behaviors are one of the main determinative components of health in the prevention of many diseases. This cross-sectional study aimed to determine health-promoting behaviors and their relationship to sociodemographic variables on 330 women of reproductive age admitted to the selected primary health-care centers in Qom city (one of the biggest cities in Iran) from March 2016 to July 2016. Data were collected using the health-promoting lifestyle profile II (HPLP-II) questionnaire and the sociode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 17 publications
4
10
2
Order By: Relevance
“…Although in the initial analysis ''sufficiency of income for expenses'' showed a significant association with two subscales (spiritual growth and interpersonal relations), after adjusting the linear regression model, there is no significant relation, which is similar to another study done in Iran. 31 The result of this study also showed that students living with their family had significantly higher levels in nutrition habits and health responsibility subscales than those who did not (be dormitory). This result is consistent with others found in Japan, Turkey, Iran, and Malaysia.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Although in the initial analysis ''sufficiency of income for expenses'' showed a significant association with two subscales (spiritual growth and interpersonal relations), after adjusting the linear regression model, there is no significant relation, which is similar to another study done in Iran. 31 The result of this study also showed that students living with their family had significantly higher levels in nutrition habits and health responsibility subscales than those who did not (be dormitory). This result is consistent with others found in Japan, Turkey, Iran, and Malaysia.…”
Section: Discussionmentioning
confidence: 53%
“…Although in the initial analysis “sufficiency of income for expenses” showed a significant association with two subscales (spiritual growth and interpersonal relations), after adjusting the linear regression model, there is no significant relation, which is similar to another study done in Iran. 31…”
Section: Discussionmentioning
confidence: 99%
“…Based on various studies, lifestyle have been investigated in different countries among groups of university students, 8 elderly, 9 and reproductive age women. 1 , 10 Due to women of reproductive age, have crucial stages, including puberty, pregnancy, and breastfeeding and their health play an important role in next generation’s health. So, choosing a healthy lifestyle is a positive approach to promoting their well-being.…”
Section: Introductionmentioning
confidence: 99%
“…So, choosing a healthy lifestyle is a positive approach to promoting their well-being. 1,10 The concept of women's lifestyle is formed in a specific context and under many factors such as norms, culture, national health policies and situation, one of which is immigration. 1,11 Immigration plays a key role in shaping the lifestyle of migrant women.…”
Section: Introductionmentioning
confidence: 99%
“…1 Women are the mainstays of their family and food keeper in Iranian culture and their health is extremely important; therefore, understanding the level of their knowledge, attitude, and practice plays an important role in the health of the community and the next generations. 10,11 Traditionally, Iranians like to have home-cooked meals. However, due to globalization and the influence of western culture as well as the increasing participation of women in economic activities that reduces the time allowed for preparing homemade food, there is a slight shift in food consumption patterns among Iranian urban families in recent years, thus home-cooked foods are losing out.…”
Section: Introductionmentioning
confidence: 99%